European legal standards for local development: a community-oriented approach - Dankevych, Vitalii Ye.; Bondarchuk, Nataliia V.; Buchynska, Anna Yo.; Kostenko, Svitlana O.; Strilchuk, Vitalii A. (Journal of Community Positive Practices, 2022)
The proposed study analyses the European legal standards that define the normative and institutional foundations of modern local development, community-oriented. In particular, it is established that within the European legal space at the level of local government the paradigm of modern local community-oriented development are the ideas of sustainable development, designed to ensure balance in the triad of socio-ecological and economic relations. Based on the analysis of the provisions of European legal standards of local development, the dialectic of the relationship and interaction between the effectiveness of local forms of participatory democracy and regulatory support for inclusive processes that express the level of involvement of local communities in municipal affairs, and those of them, directly related to the peculiarities of local development. The tendency to the greening of European legal standards of community-oriented local development is established and analysed.